2005
DOI: 10.1598/rt.59.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Leyendo juntos (Reading Together): New Directions for Latino Parents' Early Literacy Involvement

Abstract: Early reading experiences in the home prepare children for formal literacy instruction when they enter school. Most practitioners and researchers support the need for educational initiatives for increasing parents' involvement in early literacy. However, there is less of a consensus about how to develop family literacy models for Latino families. Existing literature suggests that deficit‐based theories have historically shaped many programs geared toward Latino families. As an alternative, the authors propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 25 publications
0
44
0
3
Order By: Relevance
“…These social systems are embedded in the lives of students through the diverse relationships in which they engage in an ongoing basis. In educational systems, the links and interactions that affect student success include the broader culture, teacher/educators, the institution itself, and the broader community (Ortiz & Ordonez-Jasis, 2005). Then too, the type of support that students receive on and off campus, such as advising, campus experiences, and student-faculty interactions, along with student employment obligations, family responsibilities, and the cultural norms in which they operate, individually and collectively, has the potential to affect academic persistence.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These social systems are embedded in the lives of students through the diverse relationships in which they engage in an ongoing basis. In educational systems, the links and interactions that affect student success include the broader culture, teacher/educators, the institution itself, and the broader community (Ortiz & Ordonez-Jasis, 2005). Then too, the type of support that students receive on and off campus, such as advising, campus experiences, and student-faculty interactions, along with student employment obligations, family responsibilities, and the cultural norms in which they operate, individually and collectively, has the potential to affect academic persistence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In education, this is demonstrated by links and interactions that include culture, teacher/educators, and community (Ortiz & Ordonez-Jasis, 2005). The specific type of support, advising, cultural norms, and on-campus experiences students have both affect and interconnect to affect academic achievement and persistence.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…They showed that the fathers' involvement with their children, work environment, and cultural surroundings (Taylor & Behnke, 2005) modified their social roles (e.g., being a father) and behaviors in an effort to meet societal standards (Stryker & Statham, 1985). Ortiz and his colleagues (e.g., Ortiz et al, 1999;Ortiz & Ordoñez-Jasis, 2005) recommended educational activities that would improve the quality of the father-child dyads. In a later study, Ortiz (2004) showed that the fathers' involvement affected their children's education; several themes emerged from their participation.…”
Section: Research On Father Involvementmentioning
confidence: 99%
“…This may be due in part to a traditional cultural emphasis on oral storytelling (Langer de Ramírez, 1996;McDowell, Herrera-Sobek, & Cortina, 1993;Reese, 2012). Also contributing may be varying beliefs about the value of reading to children in their home language (L. M. López, 2005) as well as an at-home emphasis on other types of activities to help children develop their language and literacy skills (López-Velásquez, 2009;R. W. Ortiz & Ordoñez-Jasis, 2005;Reese & Gallimore, 2000).…”
mentioning
confidence: 99%